(untitled) (Research Journal of Padmakanya Multiple Campus, 2023)
This study attempts to describe the contribution of potato crop to generate the income of the farmers. The study has used quantitative and descriptive research design. For this, primary and secondary data were used. While collecting the data, 25 households were consulted as a sample out of 250 households. To collect the data, this study adopted interview guideline and observation checklist as tools. While analyzing the data, simple statistical tools were used. The study revealed that majority of the households used pesticides, chemical fertilizers and applied modern technology to produce the potato. The study also found that farmers were able to produce 31,300 kg potatoes and earn NRs 1,252,000 money at a time. They produced 93,900 kg potatoes and earned NRs 3,756,000 in a year. The study concludes that majority of the households were able to increase the potato productivity and their income.